2015
DOI: 10.1016/j.jobcr.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

A rare case report of Ellis Van Creveld syndrome in an Indian patient and literature review

Abstract: Ellis Van Creveld syndrome (EVC) is a rare genetic disorder having autosomal recessive inheritance affecting the Amish population of Pennsylvania in USA with incidence of 1:244,000 for the general population. This syndrome consists of characteristic features such as bilateral postaxial polydactyly, chondroectodermal dysplasia, congenital heart defects and hypoplastic nails and teeth. There are few case reports of this syndrome reported in dental literature. We report a case of a 17 year old female presenting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 5 publications
1
14
1
1
Order By: Relevance
“…There is a great variation of anatomical characteristic of lingual frenulum reported in the literature including both healthy 2-7 subjects and individuals with syndromes [23][24][25][26][27][28] . However, the literature about posterior lingual frenulum is scarce [8][9][10][11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…There is a great variation of anatomical characteristic of lingual frenulum reported in the literature including both healthy 2-7 subjects and individuals with syndromes [23][24][25][26][27][28] . However, the literature about posterior lingual frenulum is scarce [8][9][10][11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…Estudios genéticos realizados en humanos han sugerido que la anquiloglosia tiene carácter hereditario, ocurriendo con mayor frecuencia en el sexo masculino (Martinelli et al, 2013;LeTran et al, 2019), pudiendo estar relacionada con el cromosoma X y ser el resultado de mutaciones en el gen T-box, con herencia autosómica dominante y penetrancia incompleta (Klockars, 2007;Klockars & Pitkaranta, 2009;Klockars et al, 2012;Han et al, 2012;Devasya & Sarganpala, 2017). Su ocurrencia puede ser aislada (Lenormand et al, 2018) o asociada a síndromes genéticos (Soman & Lingappa, 2015;Shetty et al, 2015;Singh et al, 2017;Srivastav et al, 2019).…”
Section: Introductionunclassified
“…Ellis and Simon Van Creveld. [1] In 1964, McKusick et al, reported a large number of cases in the Amish community of Lancaster country, Pennsylvania USA with prevalence rate of 1/50,000 live birth. [2] In nonAmish population, the estimated birth prevalence is 7/1,000,000.…”
Section: Introductionmentioning
confidence: 99%
“…Around 150 cases are described in literature and not more than 25 cases have been reported in India. [1] EVCS is caused by mutations of the EVC1 and EVC2 genes and inherited by autosomal recessive mode with parental consanguinity in about 30% of cases. [3] EVCS is considered a part of an emerging class of diseases called ciliopathies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation